Perspektif Generasi Z terhadap Pemanfaatan E-Commerce, Sosial Media, Influencer dan Testimoni - Ariani, Jihan; Simamora, Virgo; Pravitasari, Endyastuti (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the influence of e-commerce, social media, influencers and testimonials in increasing the interest in buying Skincare products by Generation Z. The population of this study was all Generation Z who live in the Jakarta area, have purchased skincare products through online media at least 3 times. To obtain a representative sample, the study used a purposive sampling technique. Generation Z who met the requirements and participated as research respondents were 220 participants. The results of this study revealed that the role of e-commerce and influencers was proven to have a positive effect on increasing Generation Z's interest in buying skincare products online. Conversely, the role of social media and testimonials was not proven to have a positive effect on Generation Z's interest in buying skincare products online in the Jakarta area.